Removing of Fe, Pb and Hg from Crude Selenium by Fractional Crystallization - Bei He; Weiyi Wang; Wenlong Jiang; Baoqiang Xu; Hongwei Yang (Metals, 2023)
This paper focuses on a fractional crystallization methodology using a rotating and internally gas-cooled crystallizer to purity crude selenium. Experiments using a rotating and gas-cooled crystallizer (cooled finger) were performed. The distribution coefficients of the main impurities (Pb, Fe and Hg) in selenium were presented as a polynomial function of concentration. The experimental parameters such as crystallization temperature and rotation rate were determined and discussed. The appropriate crystallization temperature is 222 °C and the rotation rates are 120 and 300 rpm, respectively. The purity of crude selenium increased from 99.9% to over 99.997%. Compared with the traditional method such as zone melting, this method only takes less than one day to complete several purifications, and the purification effect is better than the former. The removal rates of Hg, Pb and Fe in Se are 28.70%, 97.63% and 96.28%, respectively. The direct yield of Se purified is 92.5%. This study provides an efficient process for high-purity selenium, which has important industrial applications.